1967 Summer School of Frontier Medicine: Impact on Medical Students and Indigenous Communities ... - Ross, Shelley; Campbell, Sandy; Behn Smith, Daniele (University of Alberta Library, 2010)
The poorer health status of First Nations, Inuit, Métis (FN/I/M) people in Canada is unacceptable and requires urgent attention. One potential means of improving FN/I/M health is to focus on improving training of medical students to enhance cultural safety. Experiential, community based curriculum is recommended to strengthen relationship building with FN/I/M people and promote culturally safe practice. There is a paucity of literature on previous experiential Canadian FN/I/M medical education initiatives to guide the process of undergraduate medical curriculum development, initiation and evaluation. In 1967 seventy medical students and twenty faculty members from Canadian medical schools took part in a Summer School of Frontier Medicine, held in the Northwest Territories. The program consisted of ten days spent in Inuvik attending lectures, films and discussions regarding local medical and social issues; a week of field work in small groups in small First Nations and Inuit communities throughout the ...